(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
A quasi-experimental study was conducted on 200 children in Iraq to evaluate health outcomes for children with asthma and determine the role of prevention and health education. The collection of samples was conducted at the Sadar Teaching Hospital in Najaf City, Iraq. This study encompassed a one-year research period; the PAQLQ (Patient Quality of Life) scale was utilised to evaluate the health-related quality of life of each child prior to any intervention. Lung function was also assessed by evaluating baseline asthma control in both groups using pulmonary function tests. The intervention for Group A entails the delivery of structured workshops, overseen by healthcare professionals, focusing on the management of asthma, medication adherence, and the identification and avoidance of triggers. These workshops are scheduled to be conducted on a bi-monthly basis over a period of three months, incorporating interactive presentations and printed materials. Group B will continue with the standard care protocol without any educational intervention. Post-intervention, the Quality of Life Scale will be used to assess changes in quality of life and asthma control. The present study analysed certain demographic characteristics of Iraqi paediatric asthmatic patients. The mean age, weight, and height of both groups were found to be similar. The two groups exhibited comparable symptoms of asthma, with 60% of Group A reporting coughing and 65% of Group B experiencing this symptom. Prior to the intervention, the average PAQLQ score was 3.6, indicating a significant disability. Following the intervention, a significant improvement in Group A PAQLQ scores was observed, while no change was noted in Group B. The intervention led to a reduction in the number of attacks reported, including the fact that 60% of Group A patients were taking inhaled corticosteroids. In accordance with the prevailing pedagogical methodologies, a significant proportion of Group A participants have attested to a notable enhancement in their confidence levels concerning asthma management. The utilisation of workshops and individual counselling sessions has emerged as the predominant approach, underscoring the efficacy of these educational strategies in fostering self-efficacy and control in individuals grappling with respiratory ailments. It was established that education has a substantial impact on the management of symptoms and the utilisation of medications.